A portrait of suburban women in cinema - Salgado de la Rosa, María Asunción (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2013)
In recent decades we have experienced how large extensions of residential settlements have proliferated in the periphery of our cities. This urban model has been shown not only harmful to the environment but also ideologically wrong. Designed in the USA in response to the demand for welfare of an emerging middle class, their typology was gradually penetrating the European city through cinema. Based on inflexible assumptions, it was soon revealed as an unsatisfactory model for women to whom it was theoretically addressed.